Improving Vocational School Students’ Mathematical Communication Skills Through an Open-Ended Approach - Rifai, Rusdian; Turmudi; Jarnawi Afgani Dahlan; Suhendra (International Journal of Computational and Experimental Science and Engineering, 2025)
The rapid development of technology and industry across various sectors, such as digital technology, automation, and data analytics, requires a workforce with relevant technical skills. Although Vocational Schools (SMK) aim to produce ready-to-work labor in Indonesia, data shows that the unemployment rate among SMK graduates remains high. One of the causes is the lack of mastery in applied mathematics, which is essential in many industrial fields. This study aims to analyze the effectiveness of the open-ended approach in improving the mathematical communication skills of SMK students. The research method used is a quasi-experimental design with a pretest-posttest control group. The study involves two groups: an experimental group using the open-ended approach and a control group using a direct approach. The research population consists of eleventh-grade SMK students, with a purposive sampling method applied to two classes at SMK Dwi Putra Bangsa, namely classes XI Computer Network Engineering (TKJ 1 and TKJ 2), each of 36 students. The data analysis techniques used include normality, homogeneity, and Mann-Whitney U tests to compare differences between the experimental and control groups, as the data did not follow a normal distribution. The results show that using the open-ended approach, the experimental group experienced a more significant improvement in mathematical communication skills than the control group. This improvement is evident in the higher N-Gain results of the experimental group. In conclusion, the open-ended approach has proven to be more effective in improving the mathematical communication skills of SMK students. Therefore, it is recommended that this approach be implemented more widely in SMK to enhance students’ readiness in facing the workforce’s increasingly data-driven and technology-based challenges.